The Influence of Psychological Factor on Breast Milk Production in Breastfeeding Mothers with COVID-19 Survivors in Tegal - Latifah, Ulfatul; Rahmanindar, Nora (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
The role of breastfeeding mothers very important, not only for the baby's growth but also for their own health. Lactation offers numerous health benefits, including preventing infectious diseases and reducing depression among mothers. One of the factors that affect the worsening of exclusive lactation is the anxiety felt by mothers, especially during the COVID-19 pandemic. The anxiety experienced by breastfeeding mothers is due to the their thoughts or knowledge, will transmit the COVID-19 virus to her baby through breast milk, while one of the effects of anxiety on breastfeeding mothers is that milk production isn't smooth or doesn't come out. This study aims to determine the effect of psychological factors on breast milk production in COVID-19 survivors. It's an analytic design using an observational research design with a cross sectional approach. The population study involved 46 breastfeeding Â mothers with COVID-19 survivors in Tegal with purposive sampling and Chi Square analysis test. The results showed that in mothers who didn't experience anxiety, their milk production didn't decrease, while in mothers who experienced anxiety there was reduced milk production. The results showed that there was an influence of psychological factors on breast milk production in breastfeeding mothers COVID-19 survivors with a P-value of 0.011. It's hoped that the Tegal City government will cooperate with health workers to make breastfeeding mothers with COVID-19 calmer and less anxious.